ANALISIS PERBANDINGAN VARIASI 3 FILTER PADA REKONSTRUKSI CITRA PEMERIKSAAN CT SCAN MASTOID - Sutrisno, Novianty; Ade Kusumaputra, Pramudya; Winarno, Guntur; Gunawati, Shinta (JRI (Jurnal Radiografer Indonesia), 2021)
Background : This study aims to determine the differences in the quality of anatomical image information and to determine the best reconstruction variation of the Mastoid CT scan. Methods : The design of this study was quantitative and qualitative analysis, conducted in the radiology unit of Banten Hospital with the study population was all patients who underwent a head CT scan. The sample was taken using a purposive sampling technique specifically for the Mastoid CT Scan examination with clinical mastoiditis. Image reconstruction was performed with three variations of the filter, namely bone standard, bone smooth, and bone sharp for analysis. Result : The results obtained were that there were no significant differences in the SNR values of the three filter variations, but there were differences in the CNR values of the three filter variations. Conclusion : Based on the study conducted, it can be concluded that data obtained qualitatively according to clinical and the results of interviews with ENT specialists and radiologists that the bone sharp filter gets the highest rate which is used to analyze Mastoid CT images, and it is recommended to assess mastoid CT images with clinical mastoiditis.